Pengembangan Media Miniatur Rumah Adat Batak Karo pada Pembelajaran Bangun Datar terhadap Minat Belajar Siswa di Kelas IV SD (Jurnal Sosial Humaniora dan Pendidikan, 2025)
This research is motivated by the low interest of students in learning flat building materials in mathematics learning in elementary schools. Geometry material is often considered abstract by students, so contextual and interesting learning media are needed. One alternative that can be used is local culture-based media. This study aims to develop a miniature diorama media of the Batak Karo Traditional House as a learning tool for flat building in grade IV of elementary school and to determine the feasibility of the media based on expert validation, as well as the responses of teachers and students. This research is research and development (Research and Development) with ADDIE (Analysis, Design, Development, Implementation, Evaluation). The test subjects consisted of grade IV students and teachers at an elementary school in Medan City. The validation results show that the developed media is very feasible to use. Media expert validation obtained a feasibility score of 88%, and material expert validation obtained a score of 87%. The response of teachers and students to the media was also very positive. The use of dioramas based on local culture has been proven to increase students' attraction to the material and facilitate the understanding of geometry concepts. The diorama media of the Batak Karo Traditional House is suitable for use as a thematic learning medium, especially for flat building materials in grade IV of elementary school, as well as a means of preserving local cultural values in education.